The usage of ochre at the verge of Neolithisation from the Near East to the Carpathian Basin - Kościuk-Załupka, Julia (Archaeopress Archaeology, 2023)
This volume explores the cultural meaning of ochre among the societies of the Late Epipalaeolithic/Mesolithic and the Early Neolithic from the Levant to the Carpathian Basin.